A versatile domestic ironing board - Tan, Yuan Xia (2019)
This report will cover the problems faced by users which include safety, efficiency and usability issues. For many years since the first design of ironing board, there are limited improvements made to the safety and usefulness of the equipment while keeping the cost low so that it will be readily available for average income households. Thus, the aim of this project is to design a versatile domestic ironing board that assist user to perform housework efficiently yet affordable. This project will begin with the conceptual design of the ironing board by making use of idea generation techniques such as function analysis, morphological chart and weighted evaluation matrix to finalize on the design. Next, the design is supported with theoretical calculations and finite element method analysis ran on Fusion 360 to make sure that the product is able to take the load without failing. Last but not least, a prototype was built to ensure the workability of the design and show how the prototype works during the presentation. This report will also outline the challenges faced while working on the project and some future improvements that can be made to the product to make it even more versatile.